Impact of Global Warming on livestock production and health - Krishna, Lal (Indian Farming, 2015)
India has one of the largest cattle population in the world and also has an over increasing livestock population. The reason for increase in the greenhouse gases is not only the over exploitation of natural resources, but livestock also play a role in this by emanating methane due to rumen microbial fermentation. In this climate change era, need is to evolve scientific, technological, economic and political solutions to address the challenges in the animal busbandry sector.